Hotel Industry and Regional Competitiveness: The Bibliometric Perspective of Web of Science - J. Teixeira, Sérgio; Pocinho, Margarida (Journal of Tourism, Sustainability and Well-being, 2020)
The hotel industry is certainly a key sector study for any regional competitiveness. The aim of this study is to review the extent and emerging perspectives and approaches to the hotel industry and regional competitiveness. We adopted a systematic literature review using a bibliometric approach, focusing on the creation of maps and networks of visualization of intellectual structure in the period of 18 years (2000-2018), through the Web of Science database. The author argues that the hotel industry is undoubtedly the sector linked to regional competitiveness and that is an engine of the regional economy.